Application of the elliptic approximation model for the edge turbulence rotation measurement via the poloidal correlation reflectometer in Wendelstein 7-X. (18th May 2021) - Han, X.; Krämer-Flecken, A.; Xiang, H.M.; Vécsei, M.; Knieps, A.; Windisch, T.; Anda, G.; Andreeva, T.; Bozhenkov, S.A.; Geiger, J.; Dunai, D.; Trier, E.; et al.
Abstract: The perpendicular velocity ( v ⊥ ) of turbulence is measured by means of a hopping poloidal correlation reflectometer diagnostic for the study of turbulence rotation in the plasma edge region in Wendelstein 7-X. An elliptic approximation (EA) model is applied for calculating the space-time correlation in the edge region. The v ⊥ profile is compared in the high- ι (edge ι ≈ 1.2) and limiter (edge ι < 1) configurations. It is found that the v ⊥ gradient is inversely proportional to the heating power in the high- ι configuration, which could be attributed to the turbulence activities in the plasma edge. In the limiter configuration, the v ⊥ spike is observed near the island boundary, which is corresponded to the plasma current crash. In the standard configuration (edge ι ≈ 1), the v ⊥ profile in the island region distributes as a function of the perpendicular separation. With increasing of the plasma current, the island enlarges the size as is referred from the v ⊥ scope, accompanying with steepening of the v ⊥ gradient at the boundary of the island.